(I)当n=2时,a2=a2-1+2•2•32-2=2+4=6,
当n=3时,a3=a3-1+2•3•33-2=9+18=27.
因为an=an-1+2n•3n-2,所以=+2•3n-2.
当n≥2时,由累加法得-=2+2×3+2×32+…+2×3n-2,
因为a1=1,所以n≥2时,有=1+=3n-1,即an=n•3n-1(n≥2).
又n=1时,a1=1•31-1=1,
故an=n•3n-1(n∈N*).
(II)n∈N*时,bn==,则S2n=1+++…+.
记函数f(n)=S2n-n=(1+++…+)-n,
所以f(n+1)=(1+++…+)-(n+1).
则f(n+1)-f(n)=(++…+)-1<-1<0.
所以f(n+1)<f(n).
由于f(1)=S21-1=(1+)-1>0,此时S21>1;f(2)=S22-2=(1+++)-2>0,
此时S22>2;f(3)=S23-3=(1+++++++)-3<0,此时S23<3;
由于f(n+1)<f(n),故n≥3时,f(n)≤f(3)<0,此时S2n<n.
综上所述,当n=1,2时,S2n>n;当n≥3(n∈N*)时,S2n<n.
(III)证明:对于cn==3n,有=.
当n≥2时,≤==-.
所以当n≥2时,Tn=++…+≤+(-)+(-)+…+(-)=2-<2.
且T1=<2.
故对n∈N*,Tn<2得证.